What’s in a Place Name: Reputation Components and Drivers? A Comparison of Five European Metropolises’ Perceptions - Alaux, Christophe; Carmouze, Laura; Serval, Sarah (Management international / International Management / Gestiòn Internacional, 2020)
What do individuals know or believe about a city place? What should city managers do in order to develop city branding or change the perceptions of individuals? These questions refer to the place reputation, a managerial concept that city managers can use to foster place attractiveness. This article provides new insights on place reputation investigating the perceptions of French people about five European metropolises: Amsterdam, Barcelona, Berlin, London, Paris. Findings shed light on four key components of place reputation (i.e. cultural heritage, economic vitality, quality of life, place personality) influenced by three key drivers (i.e. experience, formal and informal communication).